PERAN DIGITAL BRANDING DAN E-WOM DALAM MEMBENTUK KEPUTUSAN PEMBELIAN FASHION ONLINE - Janwari, Gita; Salsabila, Kirana; Sendi Pamungkas, Muhammad (PT. ABIG RIZKY PUBLISHER, 2026)
This study aims to analyze the influence of digital branding and electronic word of mouth (e-WOM) on online fashion purchase decisions in Indonesia. Using a quantitative associative approach, data were collected from 100 respondents through purposive sampling with criteria of consumers who had been exposed to digital branding activities and online reviews. Data analysis was conducted using multiple linear regression with SPSS software. The results show that, partially, digital branding has a positive and significant effect on purchase decisions (t = 4.247), as does e-WOM (t = 4.817). Simultaneously, both variables have a significant effect on purchase decisions, with an F-value of 118.927. The Adjusted R Square value of 0.741 indicates that 74.1% of the variation in purchase decisions can be explained by digital branding and e-WOM, while the remaining variance is influenced by other factors. These findings emphasize the importance of a consistent brand identity strategy and credible management of consumer reviews in driving transactions in the digital fashion industry.